COVID-19 The pandemic that never should have happened, and how to stop the next one (Academic Journal of Internal Affairs, 2020)
Debora Mackenzie guides the reader through the virus Covid-19 from the first moments of happening in Wuhan December of 2019 till the preparation to the next wave of the pandemic. Her book is well structured and comprehensive, at the same time it explains the recent pandemic situation within the limits of clarity. Helps to dispel misconceptions about the coronavirus and makes clear its relationship to various types of the flu. And the concluding part of the book contains conclusions on the first wave of Covid-19, and hints and predictions how to prepare for the next pandemic at social and governmental organisations level.
Keywords: Covid-19; WHO; governmental activities; rumour-mongering